Effect of Maruca vitrata (Lepidoptera: Crambidae) host plants on lifehistory parameters of the parasitoid Apanteles taragamae (Hymenoptera: Braconidae) - Dannou, E.A.; Tamò, Manuele; Agboton, C.; Huis, A. van; Dicke, M. (Wiley, 2012)
The effect of four host plant species of the herbivore Maruca vitrata Fabricius (Lepidoptera: Crambidae) on development time, longevity, fecundity and sex ratio of the parasitoid Apanteles taragamae Viereck (Hymenoptera: Braconidae) was investigated under laboratory conditions. The larvae were parasitized when in the second instar. Maruca vitrata larvae were fed with flowers of four legumes, that is, Vigna unguiculata (cowpea), Sesbania rostrata, Lonchocarpus sericeus and Pterocarpus santalinoides, or an artificial diet both before and after parasitization. The parasitoid did not develop in hosts feeding on L. sericeus or V. unguiculata at 25◦C, or on P. santalinoides at 25◦C or 29◦C. Apanteles taragamae had the shortest development time on artificial diet at both 25◦C and 29◦C while the longest development time was recorded on L. sericeus at 29◦C. Female wasps took longer to develop compared to males at the two temperatures, regardless of the feeding substrate of their host. The longevity of the wasps at 25◦C varied among feeding substrates, but not at 29◦C. Survival rate of parasitized larvae depends on the feeding substrate. Moreover, infection of host larvae with Maruca vitrata multi-nucleopolyhedrovirus (MaviMNPV) killed larger proportions of parasitized larvae at 25◦C than at 29◦C, which was likely caused by the difference in parasitoid developmental rate. The proportion of female parasitoids was lowest on L. sericeus. The daily fecundity showed a nonlinear trend regardless of the feeding substrate, indicating that A. taragamae is a pro-ovigenic species. The data support the slow growth–high mortality hypothesis.